2017
DOI: 10.1053/j.gastro.2017.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Is Required for Activation of Pancreatic Stellate Cells, Associated With Pancreatic Cancer Progression and Promotes Growth of Pancreatic Tumors in Mice

Abstract: Autophagic PSCs produce ECM molecules and interleukin 6 and are associated with shorter survival times and disease recurrence in patients with pancreatic cancer. Inhibitors of PSC autophagy might reduce pancreatic tumor invasiveness by altering the tumor stroma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
150
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(171 citation statements)
references
References 53 publications
11
150
0
Order By: Relevance
“…Thus, this work demonstrates an autophagy-dependent metabolic crosstalk between pancreatic cancer and stellate cells that supports pancreatic cancer metabolism and promotes tumor growth. In line with this work, Endo et al have recently shown that autophagy inhibition in pancreatic stellate cells decreases tumor growth in transplantation models (Endo et al, 2017). While this work did not focus on the metabolic cross-talk and focused on the role of autophagy in stellate cell activation, it confirms the importance of both stromal and tumor cell autophagy in pancreatic cancer growth.…”
Section: Autophagy and Cancer Metabolismsupporting
confidence: 64%
See 1 more Smart Citation
“…Thus, this work demonstrates an autophagy-dependent metabolic crosstalk between pancreatic cancer and stellate cells that supports pancreatic cancer metabolism and promotes tumor growth. In line with this work, Endo et al have recently shown that autophagy inhibition in pancreatic stellate cells decreases tumor growth in transplantation models (Endo et al, 2017). While this work did not focus on the metabolic cross-talk and focused on the role of autophagy in stellate cell activation, it confirms the importance of both stromal and tumor cell autophagy in pancreatic cancer growth.…”
Section: Autophagy and Cancer Metabolismsupporting
confidence: 64%
“…While the aforementioned studies have focused predominantly on the direct contribution of autophagy to the metabolism in the tumor cell itself, several studies have also shown a critical impact of autophagy on tumor growth in a cell non-autonomous manner and in many cases this is related to effects on both tumor cell and host metabolism (Endo et al, 2017; Karsli-Uzunbas et al, 2014; Katheder et al, 2017; Sousa et al, 2016). Using a tamoxifen inducible cre recombinase, Atg7 was systemically deleted in the whole body of adult mice (Karsli-Uzunbas et al, 2014).…”
Section: Autophagy and Cancer Metabolismmentioning
confidence: 99%
“…Preclinical studies have now started to emerge showing that this is possible and that targeted therapeutic strategies directed towards specific components of the stroma or pathways of CAFs can be fruitful 79–83. Furthermore, tumour cell metabolism can also be driven by PSCs,84 and autophagy is required for the activation of PSCs, tumour progression and growth 83. Importantly, CAFs can be therapeutically targeted to enhance the response to standard chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…PSCs promote the proliferation of cancer cells by secreting kindlin-2 [114]5. Autophagic PSCs produce ECM molecules and IL6 to promote the proliferation and invasion of cancer cells [115]1. PSCs promote the migration of cancer cells via EMT process [116]2.…”
Section: Interactions and Mechanisms Between Stromal Cells And Pancrementioning
confidence: 99%